Precedent and fairness - Perry, A (Cambridge University Press, 2023)
Courts in common law systems decide cases as they decided like cases in the past—even if they believe they decided those past cases wrongly. What, if anything, justifies this practice? I defend two main claims. The first is that fairness favors treating like cases alike if that means treating them correctly. The second is that, in general, a court is as likely to decide an instant case correctly as it was to decide a previous and like case correctly. Together, these claims tell us that departing from and following precedent are equally likely to yield a correct decision, whereas following precedent may also yield a fair decision. Adhering to precedent is the dominant alternative, as a result. Fairness therefore justifies the practice of precedent. While this conclusion is not original, my argument for it is.